Marvelous advertising returns? A meta-analysis of advertising elasticities in the entertainment industry - Andrea Schöndeling; Alexa B. Burmester; Alexander Edeling; André Marchand; Michel Clement (Journal of the Academy of Marketing Science, 2023)
How does advertising affect supply and demand in the entertainment industry? Different advertising and distribution mechanisms and unique product characteristics limit the transferability of findings from other industries to the entertainment industry. This meta-analysis focuses on 290 documented elasticities, drawn from 59 studies of movies and video games, and establishes new findings and empirical generalizations. First, the average advertising elasticity in the entertainment industry is .33 (method bias-corrected .20), approximately three times higher than the average identified for other industries. Second, average advertising elasticities are higher for demand (e.g., revenue) than for supply (e.g., screens). Third, elasticities of pre-launch advertising are higher than those of overall advertising budgets, but with respect to the success period, elasticities are higher for later periods, and in total, compared to the launch period. Fourth, elasticities tend to be rather recession-proof and consistent across geographic regions but decreased after the rise of social media platforms.
Keywords: 330; Meta-analysis; Advertising elasticity; Entertainment; Supply and demand